2005
DOI: 10.1007/s00449-005-0029-9
|View full text |Cite
|
Sign up to set email alerts
|

Microbial population response to changes of the operating conditions in a dynamic nutrient-removal sequencing batch reactor

Abstract: A nutrient-removal sequencing batch reactor operated with short anaerobic/aerobic cycles was subjected to different operating conditions, namely, cycle length, feeding pattern and feed composition. The changes in microbial population, as well as the contribution of microbial groups to the total nutrient removal, were estimated using the kinetic parameters obtained in this study. Denitrifying polyphosphate-accumulating organisms (DPAOs) were detected in the system, representing a fraction of 23% of phosphorus-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…This observation was slightly different from results reported in previous studies suggesting the presence of two PAO types, denitrifying PAOs and PAOs. These studies showed that denitrifying P uptake ceased, despite the presence of available nitrate due to internal PHA depletion of denitrifying PAOs, and P uptake by other PAOs continued again when oxygen was supplied (12,23,51,52). In the present study, our SBR operation showed that nitrite concentrations in the bulk solution increased concurrently with the decrease (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…This observation was slightly different from results reported in previous studies suggesting the presence of two PAO types, denitrifying PAOs and PAOs. These studies showed that denitrifying P uptake ceased, despite the presence of available nitrate due to internal PHA depletion of denitrifying PAOs, and P uptake by other PAOs continued again when oxygen was supplied (12,23,51,52). In the present study, our SBR operation showed that nitrite concentrations in the bulk solution increased concurrently with the decrease (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…Enhanced Biological Phosphorus Removal (EBPR) processes enriched with DNPAOs have been under investigation as these microorganisms possess equal potential for simultaneous phosphate uptake and nitrate removal from wastewater [1][2][3]. DNPAOs are capable of utilizing nitrate as electron acceptor instead of oxygen hence the former have been enriched by introducing an anoxic Abbreviations: COD, chemical oxygen demand; DNPAO, denitrifying phosphate accumulating organisms; OHO, other denitrifying organisms; HRT, hydraulic retention time; N2O, nitrous oxide; OTU, operational taxonomic unit; PHB, poly hydroxy butyrate; PolyP, polyphosphate; RDP, ribosomal database project; SBR, sequencing batch rector; SDNR, specific denitrification rate; TSS, total suspended solid; VSS, volatile suspended solid; yHD, anoxic yield; MLSS, mixed liquor suspended solid.…”
Section: Introductionmentioning
confidence: 99%
“…A long-term anaerobic exposure to nitrate was demonstrated to diminish the number of certain group of PAOs showing that it may inhibit PAOs activity or activate the competition between PAOs and denitrifiers [35,36]. It was also found that a significant proportion of PAOs, known as denitrifying PAOs (DPAO), has the ability to simultaneously uptake phosphorus using nitrate as a terminal electron acceptor using stored PHAs in the anoxic zone [37,38]. The DPAOs are desirable because they, as they are able to remove nitrate and phosphorus simultaneously and also, have lower cell yield and sludge production [39].…”
Section: Simultaneous Removal Of Nitrogen and Phosphorus In An Sbr Prmentioning
confidence: 94%